2012
DOI: 10.1128/aac.05575-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Trypanocidal Synergistic Activity of N -Butyl-1-(4-Dimethylamino)Phenyl-1,2,3,4-Tetrahydro-β-Carboline-3-Carboxamide Associated with Benznidazole

Abstract: American trypanosomiasis, or Chagas' disease, is caused by Trypanosoma cruzi and affects around 15 million people throughout the American continent. The available treatment is based on two nitroheterocyclic drugs, nifurtimox and benznidazole, both only partially effective and toxic. In this context, new drugs must be found. In our previous work, the tetrahydro-␤-carboline compound N-butyl-1-(4-dimethylamino)phenyl-1,2,3,4-tetrahydro-␤-carboline-3-carboxamide, named C4, showed a potent in vitro trypanocidal eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…This approach might improve the efficacy of treatment (by generating additive or synergistic effects on different pharmacological targets) and decrease the likelihood of drug resistance and toxic effects (by reducing the drug dosages or treatment durations used). Several associations of two drugs inducing limited improvements in mice [15][16][17][18][19][20] or in patients [21] have been tested. However, as far as we know, no experimental studies or clinical trials combining the already patented drugs available on the market (BZL, NFX, POS and AMB) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This approach might improve the efficacy of treatment (by generating additive or synergistic effects on different pharmacological targets) and decrease the likelihood of drug resistance and toxic effects (by reducing the drug dosages or treatment durations used). Several associations of two drugs inducing limited improvements in mice [15][16][17][18][19][20] or in patients [21] have been tested. However, as far as we know, no experimental studies or clinical trials combining the already patented drugs available on the market (BZL, NFX, POS and AMB) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The assays that are based on viability require a low dose of the test drug and several hours and even days to develop [4]. Therefore, the use of methods that require a short time are useful in avoiding undesired factors such as degradation, biotransformation and other effects on the test drug.…”
Section: Introductionmentioning
confidence: 99%
“…␤-Carboline alkaloids have drawn attention because of their biological activities against parasites of the Trypanosomatidae family, including antitrypanosomal activity (6)(7)(8)(9)(10) and antileishmanial activity (8,(11)(12)(13). A recent study demonstrated the antileishmanial and antitrypanosomal activity of a series of N-alkyl-(1-phenyl-substituted-tetrahydro-␤-carboline)-3-carboxamides, showing that compounds containing Nbutylcarboxamide groups were the most active, suggesting that these groups may improve the biological activity of these compounds (8).…”
mentioning
confidence: 99%